Lutte contre l'échec et nouvelles formes de travail scolaire : le cas d'un établissement de la banlieue genevoise - Frédérique Wandfluh; Olivier Maulini (Nantes Université, 2011)
The fight against school failure has been and still is a powerful tool for questioning and reshaping forms of school work, without opposing the intention to reform in order to do better and the intention to maintain the existing organization, while making it explicit to the students so that they can take advantage of it. We present and analyze the work and the renewal of the organization of teaching activity as they were conceived and practiced during fifteen years by an elementary school in a popular neighbourhood in the suburbs of the city of Geneva. In the framework of, and then in the margin of a reform aiming at introducing multi-year learning cycles instead of repeating classes, the teaching staff of Bachet and some partners researchers has gradually (and collectively) developed a modular organization of basic learning, based on a hierarchy of objectives et taking into account the unique needs of students. After a brief presentation of the political context and the theoretical framework of the research-action, we will demonstrate how and why the forms of school activities have progressively evolved in this school. We will then present the questions raised by the teachers in an era of increasing political control over public education, when teachers have the feeling that their autonomy and the meaning of their work might partly escape them.